Theoretical Study of Novel Microfiber-Typed Tunable Optical Attenuator - JI Yancheng; CHEN Yupei; SUN Dan; DUAN Wei (Nantong Daxue xuebao. Ziran kexue ban)
In this study, a new type of micro-nano fiber tunable optical attenuator is studied, and the model of micronano fiber probe coupler is designed with its help. By placing the tapered fiber probe at the tapered waist position and adjusting the angle between the probe and the tapered fiber, the model achieves different light attenuation. Based on the coupled wave theory and the mode-field distribution characteristics of the tapered fiber, the relationship between the coupling ratio and the coupling angle of the probe is analyzed. The simulation results show that when the coupling angle is 30°, the optical attenuator with a coupling ratio of 50% ∶50% can be obtained. At the same time, the output coupling ratio of the attenuator can be adjusted by adjusting the coupling angle between the tapered fiber probe and the micro-nano fiber. The optical attenuator with this structure can adjust or control the optical signal and reduce the complexity and cost of the attenuator.